2004
DOI: 10.1175/1520-0442(2004)017<3829:svoris>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Subseasonal Variations of Rainfall in South America in the Vicinity of the Low-Level Jet East of the Andes and Comparison to Those in the South Atlantic Convergence Zone

Abstract: Regional and large-scale circulation anomalies associated with variations in rainfall downstream of the South American low-level jet are identified and compared to those in the South Atlantic convergence zone (SACZ). Composites of precipitation associated with strong jets reveal an approximate doubling of the quantities one would expect from climatology, with an evolution of the rainfall pattern from south to north. The occurrence of extreme precipitation events follows a similar pattern. Meridional cross sect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
144
1
11

Year Published

2004
2004
2017
2017

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 194 publications
(177 citation statements)
references
References 33 publications
21
144
1
11
Order By: Relevance
“…The propagation of tropical and extratropical intraseasonal disturbances causes significant changes in regional atmospheric circulations (Jones and Carvalho 2002;Carvalho et al 2002a;Liebmann et al 2004) and in moisture transport (Herdies et al 2002) over SA that can persist from one up to five pentads (Muza et al 2009). The objective of the present study is to evaluate the transport of when convection increases over central SA during active phases of the monsoon with no evident organization of the SACZ over the ocean (LISAM IS events).…”
Section: Moisture Transport and Intraseasonal Activitymentioning
confidence: 84%
“…The propagation of tropical and extratropical intraseasonal disturbances causes significant changes in regional atmospheric circulations (Jones and Carvalho 2002;Carvalho et al 2002a;Liebmann et al 2004) and in moisture transport (Herdies et al 2002) over SA that can persist from one up to five pentads (Muza et al 2009). The objective of the present study is to evaluate the transport of when convection increases over central SA during active phases of the monsoon with no evident organization of the SACZ over the ocean (LISAM IS events).…”
Section: Moisture Transport and Intraseasonal Activitymentioning
confidence: 84%
“…These data sets have also been widely used to describe SALLJ role in the South American climate -particularly in the warm season -and its impact on the hydrological cycle of the La Plata Basin (James and Anderson 1984, Sugahara et al 1994, Rasmusson and Mo, 1996, Nogués-Paegle and Mo, 1997, Nicolini et al 2002, Marengo et al 2004, Liebmann et al 2004, among others).…”
Section: National Centers For Environmental Prediction -Ncep-or the Ementioning
confidence: 99%
“…For example, when moisture flux into southeastern South America via the low-level jet is strong, SACZ convection is weaker than normal (Sugahara et al, 1994;Liebmann et al, 1999). Moreover, Liebmann et al (2004) have shown the relationship among the SALLJ and extreme precipitation events over subtropical South America during austral summer. Using lead and lag composites of circulation for rainfall anomalies associated with the jet, they suggested that on a daily time scale, a preference for rain (no rain) in the SACZ may agree with a weak (strong) jet and dry (wet) conditions downstream of it.…”
Section: Introductionmentioning
confidence: 99%